If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 14 + -9x = 23 + -16x Solving 14 + -9x = 23 + -16x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '16x' to each side of the equation. 14 + -9x + 16x = 23 + -16x + 16x Combine like terms: -9x + 16x = 7x 14 + 7x = 23 + -16x + 16x Combine like terms: -16x + 16x = 0 14 + 7x = 23 + 0 14 + 7x = 23 Add '-14' to each side of the equation. 14 + -14 + 7x = 23 + -14 Combine like terms: 14 + -14 = 0 0 + 7x = 23 + -14 7x = 23 + -14 Combine like terms: 23 + -14 = 9 7x = 9 Divide each side by '7'. x = 1.285714286 Simplifying x = 1.285714286
| 29y+6=180 | | 2n-4=16 | | (-8)x*p=-63+p | | 10(x-2)=5(2x-5)+5 | | 4x+12=-86-10x | | 4y+13=6y+7 | | 9-(4x+7)=34-8x | | 3.5x-12=x+3 | | 17y+2=12y+4 | | 52-2x=9x+19 | | 6x+y=y | | 3x(a+12)=60 | | 13-9x=31-23x | | 2.5x+10=1.5x+17 | | w^2-6x+8=0 | | 4.5t=36 | | 6xy=7x+3y+z | | 2x^2-9x-44=0 | | 12x-1=7x+19 | | (0.15-x)*(0.15-x)= | | 17-28x=13 | | 3x-7y=-1 | | 3+7(w+4)+w= | | 8x+12=3x+57 | | 8x*x=10 | | 4a-1=2a+8 | | -9x^2-x+10= | | 6x+14=86-2x | | 2(3w-4)-5=17 | | 13x-15=12x+19 | | 4a-1=2b+8 | | 65-5x=4x+16 |